Straight to the point: targeted mRNA-delivery to immune cells for improved vaccine design - Clemente, Bruna; Denis, Maxime; Silveira, Camila Pedroso; Schiavetti, Francesca; Brazzoli, Michela; Stranges, Daniela (Frontiers in Immunology, 2023)
With the deepening of our understanding of adaptive immunity at the cellular and molecular level, targeting antigens directly to immune cells has proven to be a successful strategy to develop innovative and potent vaccines. Indeed, it offers the potential to increase vaccine potency and/or modulate immune response quality while reducing off-target effects. With mRNA-vaccines establishing themselves as a versatile technology for future applications, in the last years several approaches have been explored to target nanoparticles-enabled mRNA-delivery systems to immune cells, with a focus on dendritic cells. Dendritic cells (DCs) are the most potent antigen presenting cells and key mediators of B-and T-cell immunity, and therefore considered as an ideal target for cell-specific antigen delivery. Indeed, improved potency of DC-targeted vaccines has been proved in vitro and in vivo. This review discusses the potential specific targets for immune system-directed mRNA delivery, as well as the different targeting ligand classes and delivery systems used for this purpose.